1996
DOI: 10.1093/clinchem/42.5.803
|View full text |Cite
|
Sign up to set email alerts
|

The case for cardiac troponin T: marker for effective risk stratification of patients with acute cardiac ischemia

Abstract: Availability of markers such as cardiac troponin T (cTnT) has brought new insights into ischemic heart disease (IHD). cTnT is a distinct protein that differs from other markers in biological function, molecular mass, and cytosolic pool. cTnT has been utilized for diagnosis of acute myocardial infarction (AMI) and risk stratification of patients with IHD. For AMI diagnosis, cTnT showed high sensitivity (94-100%) but generally lower specificity (46-99%), possibly because of increases in non-AMI patients with min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
1
5
0
2
Order By: Relevance
“…Results are obtainable in 85 minutes at an estimated cost of $17.48 per reportable result. 9 A second-generation troponin T enzyme-linked immunosorbent assay has recently been developed. 10 Muller-Bardorff et al 10 were able to improve specificityusingahigh-affinitycardiacspecificantibody,M11.7,andlowerthe discriminating value to 0.1 µg/L with a turnaround time of 45 minutes.…”
Section: Immunoassaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Results are obtainable in 85 minutes at an estimated cost of $17.48 per reportable result. 9 A second-generation troponin T enzyme-linked immunosorbent assay has recently been developed. 10 Muller-Bardorff et al 10 were able to improve specificityusingahigh-affinitycardiacspecificantibody,M11.7,andlowerthe discriminating value to 0.1 µg/L with a turnaround time of 45 minutes.…”
Section: Immunoassaysmentioning
confidence: 99%
“…A positive result is obtained in patients with 0.2 ng/mL or more of cardiac troponin T in their blood, at an estimated cost of $21.65 per reportable result. 4,9 Similarly, a sensitive fluorometric sandwich enzyme immunoassay has been developed to measure cardiac troponin I. 6 This assay uses 2 monoclonal antibodies that recognize 2 different epitopes on the cardiac troponin I molecule.…”
Section: Immunoassaysmentioning
confidence: 99%
“…Because cTnI and cTnT do not normally circulate in the blood and are more (for example cTnI 13 times) abundant in the myocardium than CK-MB on a weight basis, the signal-to-noise ratio associated with cardiac troponins is much more favourable for detection of minor amounts of cardiac necrosis missed by other biochemical markers. This ability is very significant because several studies (5,9,24,36,46,48) have indicated that patients with acute cardiac ischemia in whom myocardial infarction was ruled out, but in whom the cTnT value exceeded a defined cutoff, were at increased risk for frank AMI or cardiac death. Although different cutoffs were used in these studies, metaanalysis by Wu and Lane (49) clearly demonstrated that patients with increased cTnT have fourfold increased odds for an adverse event compared with those patients for whom cTnT was negative.…”
Section: Prognostic Significance Of Cardiac Troponin Tmentioning
confidence: 99%
“…Изучение TM из различных объектов позволило разработать структурно-функциональную модель этой молекулы. TM состоит из двух α-спиральных полипептидных цепей, закру ченных друг относительно друга, и имеет вид стержня длиной около 40 [39]. Недостатком его как маркера является наличие белка и в сердечной, и в скелетной мышцах.…”
unclassified
“…Т:аТ -высокочувствительный маркер поражені: . [ миокарда при остром инфаркте и ишемических поражениях сердца [40]. Показано, что пациенты, страдающие ишемией и имеющие высокий уровень сердечного ТнТ В крови, характеризуются очень плохим щюгнозом.…”
unclassified